(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The communication barrier affects the performance a lot. Especially, the promotion of products through direct marketing should have maximum and valid information. The sales team should convey that information, which will persuade the prospects and leads to purchase the product. Initially, the sales team fails in sales performance after all the strategy applied in the market. The solution to the problem was understood by the sales team. They had aligned the informative advertisement information and persuasive advertisement information of BPL mobile ads in personal selling method. As a result, the strategy had worked and the team has got the success in sales performance. The personal communication model really helped the sales team and sales executive to increase the sales. The case background which is faced by a sales executive of the BPL mobile is understood and explained. A suitable case method is referred to construct the case study. The literatures and sources are studied to find out the probable problems and most suitable solutions. A case model (PSCPM) is developed as per the adoption of the alternative solution by the team. The practical application assignment is designed for the management students for the academic purposes. The same model and evaluation of assignment will be useful for the industry, which possess the direct marketing activities.